¡Vamos! Let's cross the bridge - Raúl the Third, 1976- (Houghton Mifflin Harcourt, 2021)
Little Lobo and Bernabé are bringing supplies to the big celebration in the country across the bridge -- but everyone else seems to be going, too! During the long delay, they see all kinds of people on the bridge for different reasons and speaking different languages, but when someone has a grumpy moment, they all come together to make the wait as good as can be.